Predictive Role of Total Bilirubin, Alkaline Phosphatase, and Biliary Microbiota in Detecting Extra-Hepatic Biliary Obstruction - Usama Yaseen, Haleema Rafique, Zahid Rashid, Muzamil Liaqat Ali, Sajjad Hussain Sabir, Mariya Ali, Jowayria Tayrab, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Extra-hepatic biliary obstruction (EHBO) poses significant diagnostic uncertainty, particularlywhen radiologic imaging is equivocal. This prospective experimental study evaluates thepredictive power of serum total bilirubin (TBil), alkaline phosphatase (ALP), and biliary